Gerakan Bersih Kampung Sehat (G’rebek Sehat) Kelurahan Pakis Kecamatan Sawahan Kota Madya Surabaya Provinsi Jawa Timur - Erika Untari Dewi; Hendro Djoko Tjahjono; Eny Astuti; Martha Lowrani (Pelita Abdi Masyarakat, 2022)
Background: The Healthy Village Clean Movement (G'rebek Sehat) is a community service activity to improve Clean and Healthy Life Behavior (PHBS). The cause of the decline in healthy living behavior is the lack of public awareness and knowledge about clean and healthy living behavior. PHBS aims to provide learning experiences for individuals, groups, families through communication, information and education. Method: The activities of the Healthy Village Clean Movement (G'rebek Sehat) in the form of providing information on Healthy Food (SEHAT MACAN), health education about Health and Cleanliness without Cigarette Smoke (SEBENTAR KOK) and the 3M Plus Movement (KAMPUS). Result: The results obtained include knowledge of mothers after participated in counseling about healthy food, namely 54 people (53%) had good knowledge, 36 people (35%) had sufficient knowledge, and 12 people (12%) lacked knowledge, then the level of public knowledge about the dangers of smoking increased, namely, good (81%), Enough (18%), and less (1%), while public knowledge after attending counseling about 3M Plus showed that community knowledge increased, namely, good (77%), adequate (20%), and less (3%). Conclussion : This increase in knowledge motivates the community that health starts from the behavior of each individual which will shape it into family behavior and will eventually become behavior in a society.